DESCRIPTION OF PUBLIC KNOWLEDGE OF THE ISLAND REGION IN MANAGING EMERGENCY RESULTING FROM VENOMOUS SEA ANIMALS - Muthia Deliana; Dewi Puspa Rianda; Santa Novita Yosephin Silalahi (Bajang Institute, 2021)
The Riau Archipelago has a coral reef ecosystem with a diversity of marine life so that it has the potential to develop marine tourism areas and the livelihoods of the community in general are fishermen, one of which is Bintan Island. Some of the marine life in Bintan Regency are venomous marine animals that can attack humans. The sting of a venomous marine animal is an emergency condition that can be life threatening. The purpose of this study was to describe the knowledge of the people of the archipelago in handling emergencies due to venomous marine animal stings. This type of research is quantitative and the research design used is simple descriptive ie data collection is done at one time . The sampling technique used is non-probability sampling , namely convenience or accidental sampling . Data were collected by distributing questionnaires and direct interviews. Data analysis using Univariate Analysis. The results of this study indicate that the description of the level of public knowledge about venomous marine animal stings is seen based on the level of age, sex, education, occupation, income , sources of information and knowledge. Supported by the level of community knowledge in the sufficient category , as many as 36 people ( 73.5 %). The results of the study concluded that the higher a person's level of knowledge, the more alert and careful of venomous marine animal stings